2007
DOI: 10.1590/s0100-879x2006005000150
|View full text |Cite
|
Sign up to set email alerts
|

Male gonadal function, prolactin secretion and lactotroph population in an experimental model of cirrhosis

Abstract: Liver cirrhosis, a highly prevalent chronic disease, is frequently associated with endocrine dysfunctions, notably in the gonadal axis. We evaluated lactotroph population by immunohistochemistry, gonadotropins and prolactin by immunoradiometric assay and testosterone and estradiol by radioimmunoassay in adult male Wistar rats with cirrhosis induced by carbon tetrachloride. No significant difference in mean ± SEM percentages of lactotrophs was found between cirrhotic animals and controls (N = 12, mean 18.95 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Portal hypertension can lead to a diversion of blood flow from the liver to peripheral tissues, resulting in a further increase in the conversion of steroids into estrogens 8 . Although some studies 2,19,20 have established a correlation between increased PRL in cirrhosis and hyperestrogenemia, the mechanism that leads to hyperprolactinemia is not yet clear.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Portal hypertension can lead to a diversion of blood flow from the liver to peripheral tissues, resulting in a further increase in the conversion of steroids into estrogens 8 . Although some studies 2,19,20 have established a correlation between increased PRL in cirrhosis and hyperestrogenemia, the mechanism that leads to hyperprolactinemia is not yet clear.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…It is speculated that liver cirrhosis alone can cause a malfunction of the hypothalamicpituitary-gonadal axis 1,3,10 . Furthermore, high circulating levels of estradiol and prolactin also contribute to hypogonadism 2,3 , either by regulatory suppression or by direct inhibition of the testicular function 10 . The results also showed that both the PRL and E2 were at levels above normal in patients with end-stage liver disease, with normalization after OLT, in line with previous studies 1,17,18 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cirrhosis is associated with endocrine dysfunction, notably in the gonadal axis (28). Patients with liver failure have low levels of LH and FSH (11).…”
Section: Discussionmentioning
confidence: 99%
“…FSH, also called gonadotropin because it stimulates the gonads, is produced in the anterior pituitary gland of the brain (74). Several studies demonstrated that liver cirrhosis is associated with endocrine dysfunction, notably in the gonadal axis (75). Patients with liver damage have low levels of LH and FSH (76).…”
Section: Other Sex Hormonesmentioning
confidence: 99%